UNDANG-UNDANG CIPTA KERJA DAN DAMPAKNYA TERHADAP MASALAH LINGKUNGAN - Raesitha Zildjianda; Iskandar Muda; Dian Herlambang (Universitas Labuhanbatu, 2023)
With the passage of the Job Creation Law in October 2020, it has given rise to new polemics in it, one of which is the problem with the environment. Several provisions in the Draft Job Creation Law (Cipker) have clearly illustrated that the government only focuses on the growth of the country's economy, without further consideration of the ease of investment licensing that adversely affects the environment so that it harms the general public. One of the concerns in the Job Creation Law is the environmental licensing rules for business actors. The various rules in the Act have cut some of the bureaucracy in investments that intersect with the environment. Now, investment permits are no longer uniform, but risk-based. Likewise, there have been a number of changes in the assessment procedure of the Environmental impact Analysis. This paper examines changes in environmental licensing in the Job Creation Law and their impact on the environment. By using qualitative research methods. Keywords: Investment, Environment, Job Creation Law